P46 The management of abnormal lfts in an hiv positive pregnant woman. (18th May 2015) - Fraser, Gillian; Winter, Andrew; Cantwell, Roch; Mactier, Helen; Ellis, Elizabeth
Abstract : Background: Acutely deranged liver function tests (LFTs) in HIV positive pregnant women present challenges in balancing pregnancy-related conditions, antiretroviral (ARVs) toxicities and prevention of mother to child transmission (MTCT). A 34 year old HIV positive lady with a history of poor engagement in care, psychosis, cognitive impairment and recent nevirapine resistance was admitted at 26 weeks gestation under mental health legislation due to cognitive impairment and self-neglect. Method: She was commenced on darunavir/ritonavir 600 mg bd, truvada and raltegravir but three weeks later, at 29 weeks gestation, she developed rapidly progressive hepatic transaminitis. Abdominal ultrasound scan was normal and tests for viral hepatitis negative. Pre-eclampsia was excluded, leaving three working diagnoses: drug-induced hepatitis, obstetric cholestasis or acute fatty liver of pregnancy. ARVs were stopped but transaminases continued to rise (ALT 614 and AST 716 U/L). Clotting screen and platelet count remained normal but the patient began to complain of epigastric pain. HIV viral load had risen to 241 copies/ml. In view of deteriorating maternal health and the increasing risk of MTCT (HIV viral load expected to rise), the baby was delivered at 31 weeks' gestation by semi-elective caesarean after a course of antenatal steroids. The baby received antiviral prophylaxis in the form of abacavir, lamivudine and zidovudine; HIV RNA was undetectable at three months (MTCT extremely unlikely). Nine days after delivery the patient's LFTs normalised. Conclusion: Darunavir-induced hepatitis typically presents with increased AST and ALT. In this case, LFTs only started to improve following delivery of the baby, suggesting a pregnancy related cause.